Climate, diet, and nutrition drive gut microbiome variation in a fruit-specialist primate - Nina Beeby; Lahitsara Jean Pierre; Razafindraibe Faustin Jean Guy; Rakotonjatovo Justin; Tombotiana Aimé Victor; Giulia Rossi; Lotte van den Hout; Jessica M. Rothman; Katherine R. Amato; Timothy H. Webster; Andrea L. Baden (Scientific Reports)
Abstract Much of what we know about drivers of mammalian gut microbiome (GM) variation focuses on limited seasonal data, or effects of dietary fiber, particularly in leaf-eating and grazing taxa. We know little about the synergistic relationships between climate, diet, nutrition, and GM dynamics in wild mammals—particularly in fruit-eating taxa. Here, we examined GM variation across 12 months in a fruit-specialist primate, the black-and-white ruffed lemur (Varecia variegata), which is known to experience substantial environmental variation in its rainforest habitat in Madagascar. We used mixed modeling approaches to estimate the effects of climate, diet, and nutrient intakes on GM alpha diversity and differential abundances. We found substantial intra- and inter-individual GM variation. Climate and nutrient intakes impacted GM alpha diversity, and in addition to degree of frugivory and dietary diversity, each drove changes in differential abundance of unique combinations of microbial taxa. The degree of frugivory predicted few microbial abundances while nutrient intakes predicted a wide diversity, with fibers and non-structural carbohydrates showing inverse patterns to those of fat, indicating that nutrients are more important in driving the GM than simply the food types consumed. These results highlight how physiological flexibility facilitated by GM plasticity may be key to fruit-specialists’ survival of fruit scarcity.